(untitled) (Historia, 2021)
This mammoth publication can be regarded as a magnus opus by Johan Bergh, emeritus professor in the Department of Historical and Heritage Studies, University of Pretoria. As the title indicates, the publication contains a huge selection of the vast body of available material on Paul Kruger’s life and work. The original Afrikaans/Dutch edition is entitled, Paul Kruger: Toesprake en Korrespondensie van 1881–1900 and was published by Protea, Pretoria, in 2017. This English edition is an expansion of the documents on Kruger and covers the period 1850 to 1904. The documents were sampled from a wide array of sources and depositories: previous documentary publications on Kruger in the National Archives of South Africa (NASA), most of them in the Transvaal Archives series, newspapers, British Blue Books, published Transvaal Volksraad Minutes, the National Library of South Africa in Cape Town, the Jagger Library of the University of Cape Town, the University of the Witwatersrand De Souza Collection, the NZAV Archive in Amsterdam in the Netherlands, the Free University of Amsterdam, the University Library of Leiden and Gemeentearchief Kampen, the Archives of the Nederlandsch-Zuid-Afrikaansche Vereeniging in Amsterdam, the Free State Archive Depot, ZAR Green Books, the Ditsong National Museum of Cultural History in Pretoria and the Rothschild Archive in London.